(untitled) (Educação e Pesquisa, 2019)
This article is an exploratory study on the empirical field of education. The construction of the research object aimed to “put theoretical objects into play” and operate with the concepts of Pierre Bourdieu. The research object is the universities in the composition of the academic-scientific hierarchies, which is also embodied in the volume and structure of capital of their researchers with Research Productivity 1A (PQ-1A) and Senior Productivity (PQ-Sr) fellowships of Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq − National Council for Scientific and Technological Development). Its development drew on readings of reference texts and collective debates on the work of Bourdieu entitled Os usos sociais da ciência: por uma sociologia clínica do campo científico (The social usages of science: a clinical sociology of the scientific field), the main reference used in this article. The empirical data were produced from information on Lattes Platform (CNPq) and gave rise to hypotheses about the capitalization of forces internal and external to the higher education field to characterize capital strategies and structures which guarantee (or guaranteed) prominent positions in this field. The highest levels are considered the hierarchical tops which the levels below aim to achieve, and this analysis intended to map the configuration of institutional hierarchies in the field of education. Far from seeking a conclusive analysis, this product is the first step in the construction of the research, because of the volume of information that can still be explored and of the awareness that the complexity of social phenomena makes any claim to truth in the scientific field unfeasible.